The role of intrinsic Fo and duration in the perception of stress - Rosenvold, Eva (Annual Report of the Institute of Phonetics University of Copenhagen, 1981)
It has been found previously that the intrinsic differences in Fo level and duration, existing between vowels of different tongue height, are compensated for perceptually. The present experiment aims at examining the role of the intrinsic differences in connection with the perception of stress. It is found that the Fo step required to identify a certain stress pattern is of a different physical magnitude for a low than for a high vowel. Similarly, the duration required to identify a vowel as being stressed is not the same for low and high vowels. It appears from the results that the hypothesized perceptual compensation for the intrinsic differences functions in the perception of isolated vowels as well as in the perception and identification of linguistic category stress, which in its turn is dependent on Fo and duration.